Of Mommy Tracks and Glass Ceilings : A Case Study of Men's and Women's Careers in Management - Konrad, Alison; Cannings, Kathy (Relations industrielles / Industrial Relations, 1994)
Data from a 1989 survey ofover 600 middle-level managers in a large Canadian corporation were analyzed to examine the characteristics of jobs held by career-family and career-primary men and women. Hypotheses were developed based on human capital theory, statistical discrimination theory, and gender role congruence theory. Examining career outcomes suggested that participation in household labor had a significantly more negative association with men's hierarchical level than with women's. Implications for theory and suggestions for research are discussed.